A risk index for euro-denominated assets - Jakob Lage Hansen (Danmarks Nationalbank, 2006)
This paper introduces an index that captures risk premiums of euro denominated assets based on sub-indices reflecting various credit spreads, implicit volatilities and bonds' excess return over stocks. The index reflects one common factor that accounts for general shifts in risk premiums across all markets. The development in the index is related to the business cycle, macroeconomic uncertainty and monetary policy. The risk index helps understand underlying market developments and can be applied in investment decisions - when the risk index rises (reflecting higher risk premiums), the level of the German yield curve falls, it becomes more flat and the curvature is reduced. The index also has use in the evaluation of financial stability. For instance, there is a tendency for the risk index to have more extreme tops than troughs, which indicates an asymmetry in investors' returns. Also, the covariation between sub-indices has risen since 1999, thereby indicating an increase in investors' vulnerability.
Keywords: 330; Finanzmarkt; Kapitalanlage; Risikoprämie; Euromarkt